Floral induction by biostimulation in cocoa crops (Theobroma cacao L.) - Durán Mera, Christian Alejandro; Zambrano Bosquez, Juan Pablo; Machuca Pazmiño, Carlos Enrique (ECOAgropecuaria. Revista Científica Ecológica Agropecuaria, 2023)
Cocoa in Ecuador represents one of the crops of greatest economic importance at the national level. Cocoa, like other crops, can compromise its production due to various biotic and abiotic factors and to this end, the application of various products has been implemented in order to increase its production. The objective of the research was to evaluate floral induction in response to the application of biostimulants. The present investigation was carried out in the Santa Rosa canton of the El Oro province in a cocoa plantation variety “CNN-51” that had been planted for seven years. The treatments used were: control, fulvic acid, seaweed extract + cytokinin, amino acids and amino acids + cytokinin, all treatments were applied foliarly. After 30 days of application, the variables of the number of: floral pads (CF), flowers per floral pad (FCF), open flowers (FA) and set fruits (FC) were evaluated. The results obtained demonstrated that with the application of the biostimulant of amino acids + cytochianins, the highest averages were obtained in the 4 variables evaluated compared to the control. In the variables CF, FHR, FA and FC, 107, 15, 12 and 3 were obtained respectively. From our research we can conclude that biostimulants participate in or stimulate certain physiological processes in plants, as demonstrated in our research.